Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/pon.5417
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of perceived social functioning in adolescent and young adult survivors of childhood cancer

Abstract: Objectives: Social interaction and peer relationships are critical for development, especially for adolescents and young adults (AYA). Cancer treatment may disrupt social functioning and impact quality of life. Prior research into AYA social functioning has primarily been qualitative in nature or assessed via broad measures of functioning. Given the multi-dimensional nature of social functioning, and its importance for AYA, a person-centered approach to analyses is needed. Methods: AYA survivors of childhood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…More importantly, social support not only has a direct effect on fatigue, but it also has an indirect effect through social functioning. The higher the social support, the better the social functioning ( Tao and Wang, 2010 ; Qin et al, 2018 ; Willard et al, 2020 ). Husson et al (2017) suggested that strengthening social support may help young cancer survivors better reintegrate into society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, social support not only has a direct effect on fatigue, but it also has an indirect effect through social functioning. The higher the social support, the better the social functioning ( Tao and Wang, 2010 ; Qin et al, 2018 ; Willard et al, 2020 ). Husson et al (2017) suggested that strengthening social support may help young cancer survivors better reintegrate into society.…”
Section: Discussionmentioning
confidence: 99%
“… Husson et al (2017) suggested that strengthening social support may help young cancer survivors better reintegrate into society. Victoria demonstrated that good social functioning is related to a high level of social support in adolescent and young adult survivors of childhood cancer ( Willard et al, 2020 ). A possible reason for this is that higher levels of social support may improve social functioning by promoting social contact and emotional communication, thereby reducing fatigue.…”
Section: Discussionmentioning
confidence: 99%